GamiProM: a Gamification Model based on Profile Management - Dalmina, Leonardo (Universidade do Vale do Rio dos Sinos, 2018)
The use of game design elements in non-game contexts, defined as gamification, is being increasingly used to raise the motivation and engagement of users when they have to execute a task in a non-game environment, such as the workplace, the school or a software application. However, when gamification needs to be implemented, a challenge faced by developers is to identify what game elements will effectively engage the users of a software based on their user profiles and motivational characteristics. Often, many researches tend to not include or only support the most common user types and motivational factors. In response to this challenge, this thesis proposes a generic gamification model entitled GamiProM that allows a software developer to build an adaptive gamified solution for any area by making use of ontologies and rules, aiming to provide knowledge representation as well as add a semantic value to the information generated by gamification and profile management. The model is evaluated with a correlation test that identifies the existence of any association between the basic psychological needs of the users and their motivations collected with the gamified application, developed to implement the proposed model. The results showed that the motivations collected from the gamified profiles of the users have a correlation above 80% with the basic psychological needs analyzed.
Keywords: Adaptabilidade; Gamificação; Ontologias; Personalização; Perfis de usuário; Adaptability; Gamification; Ontologies; Personalization; User profiles; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação